A methodology for integrating roadway safety hardware management into the overall highway asset management program - Madanu, Sunil; Li, Zongzhi (Midwest Regional University Transportation Center, 2008)
Over the past two decades, state transportation agencies have developed management systems as analytical tools to support investment decision-making in Statewide Transportation Improvement Programs (STIP) and long-range plans. The most common management systems dealing with physical highway assets are those for pavements, bridges, and maintenance. In addition, there are management systems handling highway system operations, namely, congestion and safety. However, most state transportation agencies have not developed adequate management systems for roadway safety hardware assets such as roadway signs; signals; lighting; support and structure for signs, signals, and lighting; guardrails, barriers, and crash cushions; pavement markings; and traffic detecting devices. Cost-effective maintenance, rehabilitation, and upgrade/replacement of roadway safety hardware elements are vital to the safe and efficient operation of highways. The study began with review of literature on roadway safety hardware management. Questionnaire surveys were conducted to synthesize the current state-of-practice for managing roadway safety hardware assets across the country. Subsequent to administering the questionnaire surveys, a structured outline of questions was prepared to help conduct case studies aimed to obtain in-depth information on safety hardware asset management programs in the 12 Midwest states defined by the U.S. Census Bureau, as well as the state of Tennessee. Based on the findings of literature review, questionnaire surveys, and case studies, a methodology was proposed for roadway safety hardware data integration, primarily focusing on inventory process, data collection, and database management; and for estimating the benefits and costs of highway safety hardware projects proposed for implementation for highway segments and intersections. Finally, a new analytical framework was proposed for long-term and short-term roadway safety hardware investment programming and project selection. The analytical framework can also be adopted by state transportation agencies for integrating roadway safety hardware and general safety management, as well as pavement, bridge, and maintenance management by simultaneously considering candidate projects associated with the corresponding types of highway assets in the optimization models for project selection.
146 p.
Keywords: Asset management; Surveys; Barriers (Roads); Case studies; Safety; Traffic control devices